Idebenone protects the kidneys of rats with renovascular arterial hypertension by inhibiting oxidative stress and apoptosis: Idebenone protects rat kidneys from hypertension damage - He, Jinsen; Huang, Lixin; Lu, Linqi (Cellular and Molecular Biology, 2024)
Here, the protective effect of antioxidant Idebenone (IDB) on renovascular hypertension was studied. The two-kidney one-clip (2K-1C) model of renal hypertension was established. The rats were divided into 3 groups: sham-operation group, 2K-1C renal hypertensive rats’ model group and model treated with IDB group. The mean arterial blood pressure (MBP) of rats was measured and pathological condition of kidney was observed by H&E staining. The change of renal damage biomarkers (Cre, BUN, urine proteins), inflammatory factors (IL-6, IL-1β and TNF-α), oxidative stress ratio and key factors (MDA, SOD and CAT) were assessed by kits. The apoptosis key proteins (BAD, BAX, Caspase9, GSK-3β) were detected via Western blot. The 2K-1C model of renal hypertension was established. IDB reduced the MBP, Cre, BUN, urine proteins and improved the pathological condition of 2K-1C kidney. IDB restrained the inflammation factors (IL-6, IL-1β and TNF-α) and oxidative stress in kidney of renal hypertensive rats’ model. Besides, IDB suppressed the expression of apoptosis key factors (BAD, BAX, Caspase9, GSK-3β) in kidney of renal hypertensive rats’ model. IDB protects the kidneys of rats with renovascular arterial hypertension by inhibiting inflammation, oxidative stress, and apoptosis. These findings might provide medication guidance for IDB in renovascular arterial hypertension.